Thoughts and Practices About SDN and NFV - Chen Li; Xiaodong Duan; Wei Chen; Weiqiang Cheng (Dianxin kexue)
The entire industry is in the period of dramatic change. Flexibility, scalability, simplicity are the basic features of future network. Customer-defined virtualized network with quality guaranty, is the key service in future network. To fulfill that, SDN and NFV seem like to be the most appreciate solution. Several SDN and NFV scenarios according to the development of relative technologies were proposed. Besides, China Mobile's thoughts and practices were introduced.